EVALUASI KINERJA SIMPANG TAK BERSINYAL MENGGUNAKAN METODE MKJI 1997 DAN SIMULASI PTV VISSIM DI JALAN BUAH BATU - Sari, Fifien Nilam; Raafidiani, Reni (Jurnal Mahasiswa Terapan, 2026)
Unsignalized intersections often experience traffic problems in the form of high delays and long queues due to conflicts between irregular vehicle movements. One of the intersections experiencing these conditions is the Buah Batu–Suryalaya–Solontongan intersection in Bandung City. This study aims to evaluate the performance of unsignalized intersections based on the 1997 Indonesian Road Capacity Manual (MKJI) method and compare it with simulation results using PTV VISSIM software. The performance parameters analyzed include capacity, degree of saturation (DS), delay, and level of service (Level of Service/LOS). The analysis results show that the existing condition of the intersection has a DS value of 0.92–1.23 with an average delay of 70–120 seconds/vehicle and service levels E to F. The results of the PTV VISSIM simulation on the existing condition show higher delays, namely 120–200 seconds/vehicle with a queue length exceeding 250 meters. The improvement scenario was carried out by adding Traffic Signal Devices (APILL) and re-simulated using PTV VISSIM. The results showed a decrease in delay to 78–187 seconds/vehicle and an increase in the level of service on several approaches, although some of the main approaches were still at LOS F. This study concluded that the addition of APILL can improve intersection performance in general, but signal timing and geometric capacity improvements are needed to optimize intersection performance.